Strontium Aluminate Cement Fundamentals, Manufacturing, Hydration, Setting Behaviour and Applications - Ptacek, Petr (IntechOpen, 2014)
Strontium aluminate cement is special inorganic cement with the properties which make it favorable for various special applications such as refractory products, macro defect free (MDF) composites, blended cements and expansive cements for high temperature applications. There is an immense number of possible combinations which can be made to prepare blended and multicomponent cements and to investigate the influence of substitutions on the properties of strontium aluminate. Divided into ten sections, this book provides the latest research achievements in many aspects of this binder. The manufacturing, the hydration process, the setting behavior and the properties are described. The book contains many original and firstly published experimental research results obtained during writing. Currently there is no comprehensive work on this topic in literature. From this point of view, the book is a pilot work on this topic and should attract the attention of researchers and bring further progress of this topic.